“Excitata est ea natio ante paucos annos singulari et eleganti ingenio Matthiae regis”: il viaggio del Volterrano in Ungheria - Budetta, Enrica (Verbum – Analecta Neolatina, 2008)
During the winter of 1479–1480, Pope Sixtus IV determined that humanist Raffaele Maffei from Volterra (1451–1522) should join the cardinal Giovanni d’Aragona, who had been sent as papal legate to Matthias Corvinus’s court. This paper illustrates Maffei’s impressions of his trip, as they emerge in a published but little known letter addressed to his friend Niccolò Lisci, as well as in the eighth book of his famous encyclopedia, the Commentarii Urbani. Although the Hungarians’ bellicose nature and their Spartan habits impressed the Italian humanist, Maffei was truly amazed by the incredible cultural flourishing of the Corvinian court.